Korelasi Panjang-Berat dan Faktor Kondisi Ikan Sembilang (Plotosus canius) di Estuaria Kalimantan Tengah - Edison Harteman (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
The research aims were to evaluate length-weight correlationship and condition factors of Catfish (Plotosus canius) in the estuary Kahayan and Katingan river, Central Kalimantan. Results showed that the Catfish has a negative allometric growth pattern. Fish length between 764.7 to 275.7 mm (443.07 ± 106.75 mm), while the weight of the fish between 102.89-1627.17 grams (497.38 ± 328.73 gram). Correlationship weight increased linearly along with increasing length of catfish. Length growth is faster than body weight with thinner body shaped. Condition factors of Catfish indicated that younger fish was less healthy and the condition gets better with the increasing of length-weight of fish measure. Key words : Catfish, correlation, length-weight, condition factors